2014
DOI: 10.1177/1479164114524234
|View full text |Cite
|
Sign up to set email alerts
|

The flavonols quercetin and 3′,4′-dihydroxyflavonol reduce platelet function and delay thrombus formation in a model of type 1 diabetes

Abstract: Diabetes is associated with increased cardiovascular risk. We have recently shown that the naturally occurring flavonol quercetin (Que) or the synthetic flavonol 3',4'-dihydroxyflavonol (DiOHF) inhibits platelet function and delays thrombus formation in healthy mice. Therefore, the aim of this study was to investigate the effect of Que or DiOHF treatment on platelet function and ferric chloride-induced carotid artery thrombosis in a mouse model of type 1 diabetes. Diabetic mice treated with Que or DiOHF mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
0
18
0
2
Order By: Relevance
“…including in vitro platelet activation, in vivo thrombosis inhibition [21][22][23][24] and human interventional studies on CVDs [25][26][27][28] of quercetin, and in vitro platelet activation inhibition [29] of quercetin-3-O-β-D-glucoside have been reported in dozens of research papers, few or no reports exist on the in vitro actions of quercetin and quercetin-3-O-β-D-glucoside on procoagulant proteinases, fibrin polymer formation, and blood clot, the in vitro and ex vivo anticoagulation actions of quercetin and quercetin-3-O-β-D-glucoside, or the in vivo effects of quercetin and quercetin-3-O-β-D-glucoside against arterial thrombosis and acute thromboembolism models and platelet activation.…”
Section: Introductionmentioning
confidence: 99%
“…including in vitro platelet activation, in vivo thrombosis inhibition [21][22][23][24] and human interventional studies on CVDs [25][26][27][28] of quercetin, and in vitro platelet activation inhibition [29] of quercetin-3-O-β-D-glucoside have been reported in dozens of research papers, few or no reports exist on the in vitro actions of quercetin and quercetin-3-O-β-D-glucoside on procoagulant proteinases, fibrin polymer formation, and blood clot, the in vitro and ex vivo anticoagulation actions of quercetin and quercetin-3-O-β-D-glucoside, or the in vivo effects of quercetin and quercetin-3-O-β-D-glucoside against arterial thrombosis and acute thromboembolism models and platelet activation.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin is well known for its beneficial cardiovascular properties. It has been demonstrated to be effective in reducing or inhibiting platelet aggregation and activation in many studies, although the exact mechanism is not fully understood [20,21,39]. However, quercetin has a poor aqueous solubility, and cannot be directly immobilized onto the surface of biomaterials.…”
Section: Curves D and E Inmentioning
confidence: 99%
“…The coagulation assays conducted by Choi J H et al also demonstrated that quercetin inhibits the enzymatic activity of thrombin and FXa, and suppresses fibrin clot formation and blood clotting [19]. Actually, the antithrombotic effects of quercetin, including the inhibition of the platelet activation and aggregation, in vivo thrombosis inhibition, and human interventional studies on cardiovascular diseases, have been widely reported [20][21][22][23][24]. Furthermore, quercetin has other pharmacological functions, such as antioxidation [25], anti-inflammation [26], and the inhibition of smooth muscle cell proliferation and migration [27].…”
Section: Introductionmentioning
confidence: 99%
“…Ïîòàñêàëîâà Â.Ñ., Õàéòîâè÷ Ì.Â., Ïëºíîâà Î.Ì., Âàë³ãóðà Ì.Ñ. ³íîâèé ïîòåíö³àë, â³äì³÷åíà òåíäåíö³ÿ äî â³äíîâëåííÿ àêòèâíîñò³ ïðîòå¿íó Ñ òà Õ²²-à çàëåaeíîãî ô³áðè-íîë³çó, ùî ïåâíîþ ì³ðîþ óçãîäaeóºòüñÿ ç äàíèìè ³íøèõ äîñë³äíèê³â [7,12].…”
Section: òàáëèöÿ 1 õàðàêòåðèñòèêà ñèñòåìè ãåìîñòàçó ó ùóð³â ð³çíèõ ãðóïunclassified
“…Îòaeå, àíàë³ç îòðèìàíèõ ðåçóëüòàò³â ó ùóð³â ²² ãðóïè âêàçóº íà óïîâ³ëüíåííÿ çãîðòàííÿ êðîâ³, çîêðåìà çà ðàõóíîê óòâîðåííÿ çãóñòêó, çðîñòàííÿ àíòè-òðîìá³íîâî¿ àêòèâíîñò³ êðîâ³ òà â³äíîâëåííÿ àêòèâ-íîñò³ ïðîòå¿íó Ñ (â³äïîâ³äíî íà 39,5% òà 19,3%) òà ïîñèëåííÿ ô³áðèíîë³çó (íà 25%). Çðîñòàííÿ êîíöåí-òðàö³¿ ÐÔÌÊ òà çíèaeåííÿ ð³âíþ ô³áðèíîãåíó â³äîáðàaeຠïðîòèçàïàëüíèé åôåêò êâåðöåòèíó ïðè íèçüêîìó ðèçèêó êðîâîòå÷ çà óìîâ îäíî÷àñíîãî çàñòîñóâàííÿ ³ç àíòèêîàãóëÿíòàìè [6,9,12].…”
Section: òàáëèöÿ 1 õàðàêòåðèñòèêà ñèñòåìè ãåìîñòàçó ó ùóð³â ð³çíèõ ãðóïunclassified